Synthesis and structural characterization of a solvated dimorph of a hydrazonato-oxovanadium(v) complex with [OV(mu-O)VO] core - Mondal, Bipul; Banerjee, Rahul; Ghosh, Tapas (Journal of the Indian Chemical Society, 2011)
In this paper we report the synthesis and structural characterization of a different monoclinic variety of the title complex [V2O3(L)(2)], incorporating the doubly deprotonated benzoyl hydrazone of 5-chloro-2-hydroxyacetophenone (H2L) with P2(1)/c space group that showed some differences in bonding patterns in the solid state with respect to its another monoclinic variety with C2/c space group reported earlier.
Keywords: crystal structure; dimorphism; hydrazone complex; Oxovanadium(v) complex

Exploring the effect of hydroxylic and non-hydroxylic solvents on the reaction of [(VO)-O-IV(beta-diketonate)2] with 2-aminobenzoyl-hydrazide in aerobic and anaerobic conditions - Biswas, Nirmalendu; Patra, Debashis; Mondal, Bipul; Bera, Sachinath; Acharyya, Swarnali; Biswas, Anup Kumar; Mukhopadhyay, Titas Kumar; Pal, Amrita; Drew, Michael G. B.; Ghosh, Tapas (Dalton Transactions, 2017)
Refluxing [(VO)-O-IV(beta-diketonate)(2)], namely [(VO)-O-IV(acetylacetonate)(2)] and [(VO)-O-IV(benzoylacetonate)(2)], separately with an equivalent or excess amount of 2-aminobenzoylhydrazide (ah) in laboratory grade (LG) CH3OH in aerobic conditions afforded non-oxidovanadium(IV) and oxidovanadium(V) complexes of the type [V-IV(L-1)(2)] (1), [(VO)-O-V(L-1)(OCH3)](2) (3) and [V-IV(L-2)(2)] (2), and [(VO)-O-V(L-2)(OCH3)] (4), respectively. (L-1)(2-) and (L-2)(2-) represent the dianionic forms of 2-aminobenzoylhydrazone of acetylacetone (H2L1) and benzoylacetone (H2L2), respectively, (general abbreviation, H2L), which was formed by the in situ condensation of ah with the respective coordinated [beta-diketonate] in medium-to-good yield. The yield of different resulting products was dependent upon the ratio of ah to [(VO)-O-IV(beta-diketonate)(2)]. For example, the yield of 1 and 2 complexes increased significantly associated with a decrease in the amount of 3 and 4 with an increase in the molar ratio of ah. Upon replacing CH3OH by a non-hydroxylic solvent, LG CHCl3, the above reaction yielded only oxidovanadium(V) complexes of the type [(VO)-O-V(L-1)(OH)](2) (5), [(VO)-O-V(L-2)(OH)] (6) and [(V2O3)-O-V(L)(2)] (7, 8) whereas, upon replacing CHCl3 by another non-hydroxylic solvent, namely LG CH3CN, only the respective [(V2O3)-O-V(L)(2)] (7, 8) complex was isolated in 72-78% yield. However, upon performing the above reactions in the absence of air using dry CH3OH or dry CHCl3, only the respective [V-IV(L)(2)] complex was obtained, suggesting that aerial oxygen was the oxidising agent and the type of pentavalent product formed was dependent upon the nature of solvent used. Complexes 3 and 4 were converted, respectively, to 7 and 8 on refluxing in LG CHCl3 via the respective unstable complex 5 and 6. The DFT calculated change in internal energy (Delta E) for the reactions 2[(VO)-O-V(L-2)(OCH3)] + 2H(2)O -> 2[(VO)-O-V(L-2)(OH)] + 2CH(3)OH and 2[(VO)-O-V (L-2)(OH)] -> [(V2O3)-O-V(L-2)(2)] + H2O was, respectively, +3.61 and -7.42 kcal mol(-1), suggesting that the [(VO)-O-V(L-2) (OH)] species was unstable and readily transformed to the stable [(V2O3)-O-V(L-2)(2)] complex. Upon one-electron reduction at an appropriate potential, each of 7 and 8 generated mixed-valence [(L) (VO)-O-V-(mu-O)-OVIV(L)]species, which showed valence-delocalisation at room temperature and localisation at 77 K. Some of the complexes showed a wide range of toxicity in a dose-dependent manner against lung cancer cells comparable with that observed with cis-platin.
Keywords: Effective Core Potentials; Lung-cancer cells; Molecular-Orbital Methods; Non-oxido vanadium(iv); Non-Oxo; Oxovanadium(iv) Complexes; Tridentate ono ligand; Ray crystal-structure; Trigonal-prismatic Co-ordination; V-IV complex